FASCINATING READ MOVIE LIKE: PENERAPAN MEDIA SOSIAL INSTAGRAM SEBAGAI PROMOSI RUANG BACA VOKASI UNIVERSITAS BRAWIJAYA - Mega Asri, Tri; Ayu Pitaloka, Claudia; Badriyah, Lailatul; Mufidatul, Ihda (BACA: Jurnal Dokumentasi dan Informasi, 2018)
The rise of the use of social networking media instagram among modern society, especially among teenagers make the social networking media is very popular today. One of the utilization of information technology in the library is by using social media for various library interests. Included in the college library. One of the topics of promotional issues is through a film adapted from the novel. Therefore the vocational reading room using social media instagram as a communication service with users who no other is a vocational student. The targets in this campaign are the increasing number of Instagram Spreadsheet Readers, likes, comments, and hashtag # 4FAMEruangbacavokasi. In this research, researchers use qualitative research methods. Data collection is done using observation and interview techniques. Qualitative research is used because data collection is done when the research is more to throw an object such as photo challenge contest with the theme "Fascinating Read Movie Like". After the photo challenge is completed the researchers also held an interview about how the opinion of the participants in the race held in the vocational reading room. The result of this research is the implementation cycle conducted by researchers as much as four cycles. The first cycle applied 12 times post, second cycle applied 8 times post, third cycle applied 10 post and fourth cycle only 1 post. Within a period of three weeks photo challenge was held, there are eleven followers who follow this photo challenge contest. Of the total participants are drawn four winners with the most like, the most interesting photos and comments.